Metal recovery by microbial electro-metallurgy. (May 2018) - Dominguez-Benetton, Xochitl; Varia, Jeet Chandrakant; Pozo, Guillermo; Modin, Oskar; Ter Heijne, Annemiek; Fransaer, Jan; Rabaey, Korneel
Abstract: Raw metals are fundamental to the global economy as they are essential to maintain the quality of our life as well as industrial performance. A number of metal-bearing aqueous matrices are appealing as alternative supplies to conventional mining, like solid industrial and urban waste leachates, wastewaters and even some natural extreme environments (e.g. deep marine sediments, geothermal brines). Some of these sources are already managed for recovery, while others are not suitable either because they are too low in content of recoverable metals or they contain too many impurities that would interfere with classical recovery processes or would be cost-prohibitive. Microbial electro-metallurgy, which results from the interactions between microorganisms, metals and electrodes, in which the electron transfer chain associated with microbial respiration plays a key role, can contribute to overcome these challenges. This review provides the state of the art on this subject, and summarizes the general routes through which microbes can catalyse or support metal recovery, leading to nano- and macro-scale materials. Competing sorption and electrochemical technologies are briefly revisited. The relevant sources of metals are highlighted as well as the challenges and opportunities to turn microbial electro-metallurgy into a sustainable industrial technology in the near future. Finally, an outlook to pursue functional materials through microbial electrometallurgy is provided.